The influences of lime and irrigation water on arsenic accumulation of rice, maize and mungbean in the nethouse condition - Chuong, Nguyen Van (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2021)
This research found the great hold of liming, soils and irrigation water on the arsenic (As) accumulation of rice, maize and mung bean in the nethouse research. Two greenhouse experiments had various plant types of rice, maize and mung bean with two soils inside and outside the dyke, two irrigated waters of 0.0 and 200 ?g As/L and three different lime ratios (0, 7.0 and 9.0 tons CaO/ha). The whole treatments were twenty one (12 treatments of experiment 1 and 9 of experiment 2) with 4 repetitions. The results of this study showed that the lime application raised both soil pH and crop yield. The arsenic (As) absorption of plant bodies in stems and seeds inside the dyke increased from 67.8 to 68.3% higher than those outside the dyke, respectively. The arsenic contents of stems and seeds with the treatments of 200 ?g As/L irrigation water were higher from 81.5 to 89.4% than that of non As irrigation water, respectively. The lime supplementation of 7.0 and 9.0 tons CaO per ha reduced the As accumulation of stems and seeds of rice, maize and mung bean was lower than the one without lime supplement from 38.6 (stems) and 54.5 (seeds). Mung bean absorbed the highest As, followed by rice and maize with the lowest As value. However, the lime supplementation of 9.0 tons CaO/ha had so high soil pH of soil that restricted the growth and yield of crops. More different lime concentrations need to search for more new details and new discovery of positive effects of this research.